Feasibility of manufacturing combustion chambers for aeronautical use in Mexico - Romero Jabalquinto, Alonso; Velasco Tellez, Abraham; Zambrano Robledo, Patricia del Carmen; Bermúdez Reyes, Bárbara (2016)
The aeronauticalsectorisstrategically importantforthe economic development ofMexico and has grown steadily overthe last 10 years. Furthermore, it generates high added value for its products. In Mexico, the aircraft manufacturing sector mainly focuses on the fabrication of heat exchangers, seals, fuel ducts, and engine support rings. Currently, this sector is not involved in the manufacture of engine hot section components such as combustion chambers and turbine blades. Estimation of the associated costs enables assessment of the feasibility of fabricating such components. This study investigates the feasibility of establishing production lines for aeronautical combustion chamber fabrication in factories dedicated to the manufacture of aeronautical gas turbine engines.